Práticas de leitura na universidade e sua importância na formação e atuação do professor dos anos iniciais do ensino fundamental: concepções de docentes de uma escola pública do município de Santo Antônio do Içá-AM - Oliveira, Ocinei da Silva de (Brasil, 2022)
The present work of Course Conclusion is configured as a scientific production that aimed to analyze the influence of the University on the training and reading practice of teachers working at the Municipal School Professor Zenith Ramo located in the municipality of Santo Antônio do Iça, seeking to reflect on the role of reading in their formation and performance and identifying the university's influence in the formation of the subject and in their educational practices of teaching reading inside and outside the classroom. This work provided rigorous readings based on Freire (1989), Correa (2001), Leão (2016), and others, as well as field research, non-participant observation, questionnaire application, among other methods, which constituted a research of field of a qualitative nature necessary to reach the objective of the study and to understand the reality of teachers' reading practices. The study showed that the reading practices of higher education graduates, as well as their teaching practice, still differ from what they should be, as there are several difficulties encountered in the way teachers teach, which generates a low level of student reading learning. There is, therefore, a need for teacher-reader training and professional qualification, for greater interaction between university and school, but also for their commitment to improving the quality of reading teaching and to carrying out a greater number of reading projects. in universities and in public or private schools so that we have an effective education.